Development of a Module for the Preparation of Multiculturalism-Integrated History Teaching Materials Based on Historical Empathy for History Education Students - Firdaus Hadi Santosa (Fajar Historia: Jurnal Ilmu Sejarah dan Pendidikan, 2026)
This study aims to develop a module on preparing multiculturalism-integrated history teaching materials based on historical empathy for History Education students. The development employed the ADDIE model, which consists of five stages: analysis, design, development, implementation, and evaluation. The research subjects involved 10 students in a small-scale trial and 26 students in implementation trial. Data were collected through observation, interviews, expert validation questionnaires, and student learning outcome tests. The results showed that the developed module received a material expert validation score of 88.88% (very feasible category) and a media expert validation score of 84.88% (very feasible category). The small-scale trial indicated an improvement in student learning outcomes, with average scores increasing from 59.5 to 77.5, achieving an N-Gain of 0.45 (medium category). Meanwhile, the large-scale field trial showed an increase from 65.19 to 87.69, with an N-Gain of 0.51 (medium to high category). The module was declared effective and practical in enhancing students' ability to develop history teaching materials that integrate multiculturalism and historical empathy. This product is expected to be used as an alternative self-study material in higher education history courses to foster national and humanitarian awareness.